Prevalence and Antifungal Susceptibilities of Candida spp from a South Indian Tertiary Care Hospital - Swapna Kurup Rajgopal (International Journal of Medical Research and Review, 2017)
Introduction: Candida sp. is increasingly being implicated as the cause of both community acquired and Nosocomial infections. With development of new resistance patterns versus the inherent resistance present in some of the species isolated from critical care areas, the complications resulting from long term antibiotics, surgical and medical interventions and environmental colonization by the Candida sp. is becoming more prevalent.Method: Prevalence of different species and their antifungal susceptibilities grown from various samples received in 20 months were studied using semi-automated MiniAPI kits. Results of tests done on 356 isolates were collated and analysed retrospectively.Results: Of the 356 samples, C. tropicalis showed prevalence of 37.07% as compared to C.albicans 31.1%, C guilliermondii (11.8) and C parapsilosis (6.74%). Candida sp were found to sensitive to 5-Flucytocine and Amphotericin B. Resistance to Itraconazole was noted more than to Fluconazole.Conclusions: Infections with Candida spp are usually of low virulence and are associated with a few well-defined risk factors as immunocompromised state, Malignancy and steroid therapy. Understanding these risk factors, identifying the species with changing trends in antifungal resistance, instituting infection control practices to reduce morbidity and mortality in critical care areas can improve outcomes.